Handbook of Fuel Cells 2010
DOI: 10.1002/9780470974001.f205042
|View full text |Cite
|
Sign up to set email alerts
|

Macrocycles

Abstract: The catalysis of the reduction of oxygen on supported metal macrocyclics is discussed in terms of electronic interactions of the dioxygen molecules with metal centers that lead to the weakening of the OO bond and to a lowering of activation energy. Correlations between electronic properties of the macrocyclic complexes and activity are also discussed, such as the influence of the redox potential of the metal center in the electrocatalysis. The overall 2‐ versus 4‐electron reduction mechanisms on metallo‐macro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2012
2012
2012
2012

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(8 citation statements)
references
References 52 publications
1
7
0
Order By: Relevance
“…If step 7 is the rate controlling, with a symmetrical energy barrier, the Tafel slope should be 0.039 V. Many authors have reported Tafel slopes in the range 0.030–0.040 V for O 2 reduction in alkaline media catalyzed by Fe phthalocyanines or similar Fe macrocyclic complexes using graphite or carbon substrates. ,,,,,, Figure shows Tafel lines for FePc adsorbed directly on Au(111) and via molecular spacers, and in all cases the slopes are close to 0.030 V, so essentially the kinetics parameters as far as Tafel slopes are concerned do not seem to depend on the way of surface confinement of the FePc catalyst on the electrode. They give practically the same values no matter whether the substrate is graphite, carbon, gold, or gold coated with SAMs.…”
Section: Resultsmentioning
confidence: 85%
See 4 more Smart Citations
“…If step 7 is the rate controlling, with a symmetrical energy barrier, the Tafel slope should be 0.039 V. Many authors have reported Tafel slopes in the range 0.030–0.040 V for O 2 reduction in alkaline media catalyzed by Fe phthalocyanines or similar Fe macrocyclic complexes using graphite or carbon substrates. ,,,,,, Figure shows Tafel lines for FePc adsorbed directly on Au(111) and via molecular spacers, and in all cases the slopes are close to 0.030 V, so essentially the kinetics parameters as far as Tafel slopes are concerned do not seem to depend on the way of surface confinement of the FePc catalyst on the electrode. They give practically the same values no matter whether the substrate is graphite, carbon, gold, or gold coated with SAMs.…”
Section: Resultsmentioning
confidence: 85%
“…A generally accepted mechanism for O 2 reduction by Fe phthalocyanines confined to graphite or carbon surfaces ,,,,,, that seems to operate for FePc anchored to Au(111) is the following: false[ Fe ( III ) PcOH false] ads + normale false[ Fe ( II ) Pc false] ads + OH goodbreak0em1em⁣ fast false[ Fe ( II ) Pc false] ads + normalO 2 false[ Fe III normalO 2 false] ads goodbreak0em1em⁣ fast [ Fe III O 2 ] ads + e intermediates rds However, according to the calculated energy diagram of Figure , the formation of the adduct in step 5 will slow the reaction instead of catalyzing it because the energy barrier is larger as compared to that where the initial reactants proceed directly to the formation of the adduct, concerted with the transfer of one-electron. S...…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations